Typology of Witchcraft in Ukrainian and Russian Prose of the 1st Half of the 19th Century: Anthropology, Stereotyping, Semantics - Chyk, Denys; Dzys, Taras (Slavia Centralis, 2022)
The authors analyse the texts of Ukrainian and Russian writers of the nineteenth century, in which the witchcraft theme became the subject of imaginative interpretation in some way. The range of witchcraft theme features, its psychological and mythological foundations, anthropological poetics of the witch image, and its cultural, historical and national experience are clarified in the works. In literary images of witches the writers show the groundless and prejudiced perceptions of Roma and Jewish women as enchantresses, urged by sortilege, which was common among these nationalities. The motive of the accidental man on the witch coven, which is deployed in "The Lost Letter: A Tale Told by the Sexton of the N…Church" by N. Gogol, "The Witches of Kyiv" by O. Somov, represents people’s ideas of the witch orgies. In the familiar spirit images – helpers of witches and sorcerers – one can see a combination of two motives – turning demons into animals and people, and communication between the infernal world and a witch or sinner.
Keywords: witch; witchery; the witchcraft topos; stereotype